The Boyer-Moore prover and NUPRL an experimental comparison - Basin, David; Kaufmann, Matt (1991)
Abstract: "We use an example to compare the Boyer-Moore Theorem Prover and the Nuprl Proof Development System. The respective machine verifications of a version of Ramsey's theorem illustrate similarities and differences between the two systems. The proofs are compared using both quantitative and non-quantitative measures, and we examine difficulties in making such comparisons."
Keywords: Computer software; Mathematics; Mathematik; Automatic theorem proving